The current state of acute treatment for migraine in adults in the United States. Issue 7 (2nd October 2020) - Cooper, Wade; Doty, Erin Gautier; Hochstetler, Helen; Hake, Ann; Martin, Vincent
ABSTRACT: Migraine is a common and disabling disorder with substantial personal, social, and economic burden that affects 37 million people in the United States. Risk factors for migraine include age, sex, and genetics. The goal of acute treatment of migraine attacks is to stop the pain and associated symptoms of the migraine attack and return the patient to normal function. The acute treatment landscape for migraine has recently expanded beyond the standard nonsteroidal anti-inflammatory drugs, analgesics, triptans, ergotamines, and combination therapies, to include neuromodulation devices, and recently approved calcitonin gene-related peptide receptor antagonists and a serotonin (5-HT1F ) receptor agonist. Unmet acute treatment needs still exist due to lack of efficacy, unwanted side effects, or contraindication to treatment. Effective treatment of migraine requires the clinician to assess the patient, make an accurate diagnosis, and then offer appropriate therapy based on the patient's medical history, comorbidities, and preferences, as well as published clinical evidence. The objective of this narrative review is to familiarize primary care clinicians with the variety of acute treatment options available in the United States today based on clinical trial findings, meta-analyses, evidence-based guidelines, and professional society consensus statements.